Network Hypervisors pros and cons: A survey - Sasibhushana Rao, P; Kalyan Chakravarthy, C (International Journal of Computer Sciences and Engineering, 2025)
In networking environment due to increasing demand of resources reliability, load balancing and efficient routing of data are still becoming a major issue. So I am proposing an efficient approach for solving all these issues using an innovative technique called Software Defined Networks(SDN).Software Defined Networks (SDN) has evolved as an emerging research area where it provides efficient network resources by separating data plane from control plane. Network virtualization allows sharing of physical resources by different users where each user executes their applications over its virtual network and its main features are isolation, multitenancy and simplified segmentation. The main component for virtualizing SDN is Hypervisor that abstracts physical SDN’s into isolated virtual SDN’s having its own controller. This paper presents different network hypervisors and its comparison shown will have a great impact on researchers building an efficient network infrastructure.